Does the timing of measurement alter session-RPE in boxers? - Uchida, M. C.; Teixeira, L. F. M.; Godoi, V. J.; Marchetti, P. H.; Conte, M.; Coutts, A. J.; Bacurau, R. F. P. (Journal of Sports Science & Medicine, 2014)
The purpose of this study was to compare the influence of measuring the overall session rating of perceived exertion (session-RPE) at 10 vs. 30 minutes following exercise. Eight boxers completed three different standardized training sessions of different intensities (easy, moderate and hard) in a matchedpairs, randomized research design. Exercise intensity was assessed during each bout by measuring heart rate, blood lactate concentration and session-RPE. To assess the effect of measurement timing on session-RPE, RPE data were collected either 10 or 30 minutes post-exercise. There was no significant effect of measurement time on session-RPE values following easy (10 minutes: session-RPE = 1.3 ± 1.0 Arbitrary Unit (AU), %Heart Rate Reserve (HRR) = 49.5 ± 11.1, and Delta Blood lactate = -2.3 ± 16.3%; 30 minutes: session-RPE = 1.7 ± 1.0 AU, %HRR = 51.3 ± 10.8, and Delta Blood lactate = 0.7 ± 25.2%), moderate (10 minutes: session-RPE = 2.7 ± 1.6 AU, %HRR = 67.2 ± 10.8, and Delta blood lactate = 2.2 ± 19%; 30 minutes: session-RPE = 2.5 ± 0.9 AU, %HRR = 67.2 ± 5.9, and Delta Blood lactate = 24.5 ± 17.1%) and hard (10 minutes: session-RPE = 5.7 ± 1.0 AU, %HRR = 88.1 ± 6.3, and Delta Blood lactate = 146.3 ± 87.9%; 30 minutes: session-RPE = 5.8 ± 1.9 AU, %HRR> = 83.3 ± 8.0, and Delta Blood lactate = 91.6 ± 39%) sessions. In conclusion, our findings suggest that session-RPE can be used in boxing training routines across a range of intensities and accurate measurements can be determined as early as 10 minutes after exercise.